Peran Guru PGMI Menanamkan Nilai-Nilai Toleransi Pada Anak Usia Sekolah Dasar Negeri 0723 Parmainan - Rizki Hamdan Saputra; Fatimah Fatimah; Yusliana Yusliana; Tutut Yuliani Pertiwi; Candrika Evayanthy Hasibuan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
PGMI teachers play a strategic role in shaping children's character and instilling values of tolerance through learning and role modeling in the elementary school environment. This study aims to describe how PGMI teachers play a role in instilling values of tolerance in students at MI 0723 Parmainan. This study uses a descriptive qualitative approach. Research informants consist of several classroom teachers and subject teachers. Data collection techniques were conducted through in-depth interviews. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The research results indicate that teachers instill tolerance values through a multicultural education approach and contextual learning strategies, such as group discussions, case studies, picture stories, and the integration of values into subjects like Civic Education, Social Studies, and Islamic Education. Teachers also emphasize the importance of respecting differences, building empathy, and fostering mutual respect in the school environment. These findings confirm that the instillation of tolerance values can be done flexibly, integrally, and contextually through various learning activities in elementary schools.